PENGARUH CORPORATE GOVERNANCE TERHADAP INTELLECTUAL CAPITAL DISCLOSURE - Nurdiana Indah; Sri Handayani (Diponegoro Journal of Accounting, 2017)
The aims of this study is to examine the effect of corporate governance on intellectual capital disclosure. The population in this study are all of listed firms in Indonesia Stock Exchange in 2013, 2014 and 2015. The sampling method in this study is purposive sampling. Criteria for the firms sample is which companies included in the index KOMPAS 100. And at the last, this study used 274 firms-years observations. The analysis technique used is multiple regression. The analysis showed that independence of the board of commisioners, the number of board meetings, the number the board of directors, audit committee size and concentration of ownership have not possitively significant effect on intellectual capital disclosure. The variable frequency of audit committee meetings have positive and significant effect on intellectual capital.